2020
DOI: 10.1002/asi.24393
|View full text |Cite
|
Sign up to set email alerts
|

Loosen control without losing control: Formalization and decentralization within commons‐based peer production

Abstract: This study considers commons-based peer production (CBPP) by examining the organizational processes of the free/libre open-source software community, Drupal. It does so by exploring the sociotechnical systems that have emerged around both Drupal's development and its face-to-face communitarian events. There has been criticism of the simplistic nature of previous research into free software; this study addresses this by linking studies of CBPP with a qualitative study of Drupal's organizational processes. It fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Research on how self-organization occurs in CBPP communities has shown that-counterintuitively to the initial accounts criticized by authors such as Viégas et al (2007) or Mateos-García and Steinmueller ( 2008)-the changes experienced in the self-organizational processes of CBPP communities tend to show an increase in the degree of formalization around decision-making over time when they grow, which is explained as a means to achieve decentralization and to scale up communities (e.g., Forte et al, 2009;Rozas & Huckle, 2021;Schweik & English, 2013). This has been identified even in cases with a generally antibureaucratic attitude, such as communities with a strong hacker culture which aim to avoid formal and bureaucratized systems (Rozas, 2017).…”
Section: Self-enforcement and Formalization Of Rulesmentioning
confidence: 92%
See 2 more Smart Citations
“…Research on how self-organization occurs in CBPP communities has shown that-counterintuitively to the initial accounts criticized by authors such as Viégas et al (2007) or Mateos-García and Steinmueller ( 2008)-the changes experienced in the self-organizational processes of CBPP communities tend to show an increase in the degree of formalization around decision-making over time when they grow, which is explained as a means to achieve decentralization and to scale up communities (e.g., Forte et al, 2009;Rozas & Huckle, 2021;Schweik & English, 2013). This has been identified even in cases with a generally antibureaucratic attitude, such as communities with a strong hacker culture which aim to avoid formal and bureaucratized systems (Rozas, 2017).…”
Section: Self-enforcement and Formalization Of Rulesmentioning
confidence: 92%
“…Second, a blockchain as a common database infrastructure generates affordances for interoperability beyond the boundaries of a particular CBPP community. For example, a set of smart contracts which encode agreements between community networks, or by reflecting the decisions made by different community networks with regards to their different notions of value (Rozas et al, 2021) and ways to make them interoperable (De Filippi & Hassan, 2015). Nevertheless, as with the previously discussed affordances, the processes related to the codification of trust in ways that facilitate interoperability between and within CBPP communities will remain as social processes of negotiation.…”
Section: Codification Of Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Contribution activities related to source code (SG 1.1 ) are further classified into three subgroups: core (SG 1.1.1 ), contributed (SG 1.1.2 ), and FLOSS custom projects (SG 1.1.3 ) not included in Drupal.org. The reason for this distinction is the significant differences found in the organizational aspects of the sociotechnical systems that surround these contribution activities (Rozas and Huckle, 2021), despite the type of object being the same: source code. For example, the possibility of performing modifications in the digital commons for the core group is more formalized, typically harder to achieve, and more specialized.…”
Section: Findings "Object-oriented" and "Community-oriented" Contribumentioning
confidence: 99%
“…For example, DrupalCon activities, largely organized by the most formal institution within the Drupal community, the Drupal Association, are at the formal end of the spectrum. As in the case of the subgroups of G 1 , organizational processes with a higher degree of complexity in G 2 involve significant organizational changes overtime, including more clearly defined roles (Rozas and Huckle, 2021) and the emergence and perception of new activities which are valued as contributions, such as the peer reviewing and selection of presentations carried out by "track chairs, " as I 10 explains: Then, track chairs can go through them, and decide. There are two or three chairs for each track.…”
Section: Findings "Object-oriented" and "Community-oriented" Contribumentioning
confidence: 99%